Poteri, relazioni, guerra nel regno di Ferrante d'Aragona Powers, relationships, and war in the reign of Ferrante d'Aragona - Francesco Senatore (Clio: Saggi di scienze storiche, archeologiche e storico-artistiche, 2011)
This volume collects a series of studies revolving around the edition of Milanese and Florentine diplomatic correspondence from Naples in the Aragonese age, particularly in the years of Ferrante d'Aragona (1458-94). They range from the history of war and territory to prosopography, from the reconstruction of relation networks in courts to international politics, from feudal geography to the conflicts between monarchy and aristocracy. This results in an important increase in our knowledge of the Kingdom of Naples, made possible by the extensive and systematic study of the diplomatic sources, which is evaluated in its different degrees of reliability also thanks to the support of the other sources available − from both within and without the kingdom − used in the full range of its informative potential.